Державний фінансовий контроль у бюджетній сфері - Микитюк, Ігор; Mykytiuk, Ihor (ТНЕУ, 2018)
Визначено сутність державного фінансового контролю у бюджетній сфері, його мету та завдання; напрями діяльності органів державного фінансового контролю – Рахункової палати, Державної аудиторської служби України та Державної казначейської служби України. Здійснено аналіз порушень бюджетного законодавства. Визначено ефективність контролю та перспективи його розвитку. Introduction. The transition to the program budget in the public finance sector, the strengthening of the fight against corruption and offenses in the budget sphere attach particular importance to the problems of improving the management of financial resources. In this regard, the problem of efficient formation and spending of budgetary funds is relevant. Purpose.The purpose of the article is to reveal the essence of the state financial control in the budget sphere and develop practical proposals for its development. Results.The main problems of the state financial control in Ukraine should include: the fiscal nature of the overwhelming majority of control procedures; absence of system control, where the main is further control, and the procedures of preliminary and ongoing control are rather weak and unregulated; not awareness of the importance of internal financial control both in the system of management of public finances and managers of enterprises, institutions, organizations; the low level of effectiveness of the administrative penalty mechanism, when the amount of the fine for misuse or illegal use of budget funds is considerably less than the amount of budget funds that the state loses due to abuse of officials and can not provide full compensation for these losses; growth of financial irregularities in the use of budget funds; unregulated activity and cross-section of the functions of the subjects of financial control; weak interaction between externaland internal control bodies. The formation of the mechanism for its implementation should be based on a set of principles that reflect the main properties of the system being created in the scientific, methodological, legal and organizational aspects. It is this hierarchy of structuring that is justified and rational. The group of scientific and methodological principles include the following: systemic, complexity, purposefulness, continuity. The set of legal principles includes: legality, unity, prerogative of national interests. Our organizational principles include: parity, objectivity and competence, budget efficiency, preventive, interaction between public authorities and local self-government. In the process of forming a mechanism for the implementation of financial control must take into account its dual economic orientation. First, it must ensure the rational use of financial resources, which is expressed in minimizing budget expenditures. Secondly, the effectiveness of control activities manifests itself in the strictly targeted use of state resources with high economic efficiency of the corresponding investments. Thus, the criterion for evaluating the rationality of the implementation of financial control is the quantitatively expressed correlation between the target consumption of public funds and the stable replenishment of budgetary resources. Conclusion. The current practice of conducting financial audits confirms the existence of complex problems in the budget sphere. The following typical violations such as non-targeted, unlawful and inefficient spending of public funds are fairly common. At present, in the arsenal of controlling bodies, largely outdated forms and methods of audits and audits prevail. Their focus is mainly on identifying the facts of violations, and not the reasons for their occurrence, which does not contribute to successfully overcoming the disadvantages of using budget funds. A transition to a higher level of quality control and revision work with the use of modern instruments of monitoring and auditing, achievements of domestic and foreign economic science is necessary. Continuing scientific research, it is advisable to focus on the mechanisms of using new approaches to the management of the system of state financial control bodies as a practical tool for ensuring the efficiency of spending budget funds.
Increase of stimulant influence remittances from abroad
Keywords: бюджетна сфера; бюджет; державний фінансовий контроль; бюджетні кошти; бюджетні правопорушення; budget sphere; budget; state financial control; budgetary funds; budget violations